Optimizing T cell transduction: a novel transduction device for efficient and scalable gene delivery - Kang-Zheng Lee; Tan Dai Nguyen; Dan Liu (Journal of Translational Medicine)
Abstract Background Viral transduction is a critical step in the manufacturing of genetically modified T cells for immunotherapies, yet conventional transduction methods suffer from low to medium efficiency, high vector consumption, and limited scalability. Methods To address these challenges, we introduce the Transduction Boosting Device (TransB), an innovative, automated, and closed-system platform designed to enable efficient and scalable gene delivery and overcome the limitations of conventional transduction methods. TransB improves cell-virus interactions by facilitating proximity between target cells and viral vectors. Results TransB demonstrated up to 1-fold decrease in processing time, 3-fold reduction in viral vector consumption, and 0.7-fold increase in transduction efficiency compared to 24—well plate method for donor T cell transduction in studies evaluating its impact on transduction process. Comparison studies transducing T cells from three different donors with Lenti-GFP vectors showed that TransB achieved an average 0.5-fold improvement in transduction efficiencies while maintaining comparable post-transduction cell recovery, viability, growth, and phenotype compared to 24—well plate. Furthermore, TransB delivered consistent performance across two different input cell numbers demonstrating scalability of the process. Conclusion These findings suggest that TransB could significantly shorten the transduction time, reduce the transduction cost and improve the transduction efficiency for manufacturing genetically modified T cell therapies. It shows strong potential as a robust, efficient, and scalable platform to enhance T cell therapy manufacturing and help overcome current manufacturing challenges in the field.